2019
DOI: 10.1021/acsomega.9b02658
|View full text |Cite
|
Sign up to set email alerts
|

Fabricated Electrochemical Sensory Platform Based on the Boron Nitride Ternary Nanocomposite Film Electrode for Paraquat Detection

Abstract: Hexagonal boron nitride (BN), an effective diffusion material for mass transport, was functionalized with molybdenum disulfide (MoS2) and Au nanoparticles (Au NPs). Then, the working electrodes with developed nanomaterials were applied to construct an electrochemical paraquat sensor. BN was prepared using a solid-state synthesis method combined with solvent-cutting. The electrochemical properties of the BN/MoS2/Au NP-based glassy carbon electrode (GCE) were investigated using differential pulse voltammetry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Since paraquat is considered a non-polluting herbicide, it is often used indiscriminately, increasing its toxicological potential and the risk posed to human health. Consequently, many studies have demonstrated the detection of paraquat using different electrodes, such as modified glassy carbon electrodes [21][22][23][24][25][26], hanging mercury drop electrodes [27], and screen-printed electrodes [28,29]. These reported devices, however, suffer from high material and manufacturing costs, have poor disposability, are not suitable for portable detection, and involve complex electrode modification steps in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Since paraquat is considered a non-polluting herbicide, it is often used indiscriminately, increasing its toxicological potential and the risk posed to human health. Consequently, many studies have demonstrated the detection of paraquat using different electrodes, such as modified glassy carbon electrodes [21][22][23][24][25][26], hanging mercury drop electrodes [27], and screen-printed electrodes [28,29]. These reported devices, however, suffer from high material and manufacturing costs, have poor disposability, are not suitable for portable detection, and involve complex electrode modification steps in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Paraquat (1,1-dimethyl-4,4-bipyridine dichloride, PQ) is a kind of herbicide that has been widely used in a variety of applications, such as broad weed control and desiccants on crops [ 1 , 2 ]. Paraquat, also known as methyl viologen, is one of the active components of dipyridine compounds [ 3 ], which are easily reduced to stable free radicals and cause severe toxicity to humans and animals [ 4 ]. It has been proven that PQ may cause serious damage to the lungs, liver, kidney and heart, and also lead to neurodegenerative diseases such as Parkinson’s disease [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 At present, there are many methods to detect pesticides, such as gas chromatography−mass spectrometry, 9,10 liquid chromatography−mass spectrometry, 10,11 surface-enhanced Roman spectroscopy, 12,13 and electrochemical methods. 14,15 Although these methods are sensitive and accurate, they require expensive instruments, complex pretreatment, or highly trained technicians, making them unsuitable for low-cost and on-site analysis. Thus, it is essential to develop a rapid, simple, and portable analysis method for real-time and on-site monitoring of PQ.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the maximum dose of PQ is approximately 0.05 mg/kg in leafy vegetables and 0.01 mg/kg in pulp fruit (GB 2763-2021). Besides, the U.S. Environmental Protection Agency (USEPA) limit of PQ residues is 200 μg/L (7.8 × 10 –7 M) in drinking water. , At present, there are many methods to detect pesticides, such as gas chromatography–mass spectrometry, , liquid chromatography–mass spectrometry, , surface-enhanced Roman spectroscopy, , and electrochemical methods. , Although these methods are sensitive and accurate, they require expensive instruments, complex pretreatment, or highly trained technicians, making them unsuitable for low-cost and on-site analysis. Thus, it is essential to develop a rapid, simple, and portable analysis method for real-time and on-site monitoring of PQ.…”
Section: Introductionmentioning
confidence: 99%